The Effectiveness of Poundfit Exercise as High-Intensity Interval Training (HIIT) on Stress And Anxiety Levels among Young Adult Women with A Sedentary Lifestyle - Dina P. Sari; Upik Rahmi; Lina Anisa Nasution; Suci Tuty Putri (GLOBAL HEALTH SCIENCE GROUP, 2026)
Stress and anxiety are increasingly prevalent mental health problems among young adults, particularly those with sedentary lifestyles. High-Intensity Interval Training (HIIT) is recognized as an effective non-pharmacological approach to improve mental health outcomes. Poundfit is a music-based HIIT exercise that combines rhythmic movements and high-intensity physical activity, which may provide optimal psychological benefits. This study aimed to analyze the effectiveness of Poundfit exercise in reducing stress and anxiety levels among young adults with sedentary lifestyles. This study used a randomized controlled trial (RCT) design with a pretest–posttest control group model. A total of 40 young adults with high sedentary behavior were randomly assigned to an intervention group (n = 20) and a control group (n = 20). The intervention group participated in a four-week Poundfit program (12 sessions), conducted three times per week for approximately 45 minutes per session. Stress and anxiety were measured using the Depression Anxiety Stress Scale-21 (DASS-21). Data were analyzed using paired samples t-tests and independent samples t-tests, with statistical significance set at p < 0.05. The intervention group showed a significant reduction in stress and anxiety levels after completing the Poundfit program, whereas the control group did not demonstrate significant changes. Independent samples t-test results also indicated that posttest stress and anxiety scores in the intervention group were significantly lower than those in the control group. These findings suggest that Poundfit exercise is an effective HIIT-based intervention that can improve mental health outcomes among sedentary young adults. Poundfit exercise is effective as a practical and enjoyable HIIT intervention for reducing stress and anxiety among young adults with sedentary lifestyles. Further studies with larger and more diverse samples are recommended to confirm these findings and examine long-term effects.